Teachers’ Pedagogical Techniques in Delivering Speaking Assessment: Secondary Level of Education - Putri Rahmawati Oktapiani; Luthfiyatun Thoyyibah; Didih Faridah (Universitas Galuh, 2026)
Speaking assessment plays a critical role in English language teaching, especially in developing students’ oral communication skills in junior high schools. Teachers often rely on limited or repetitive speaking assessment methods, which may not fully support the development of students’ speaking skills. Therefore, this study aimed to explore the types of speaking assessment techniques used in the classroom and the considerations behind the teacher’s choices. A qualitative case study approach was employed, involving one English teacher as the participant. Data were collected through classroom observations and semi-structured interviews. The findings revealed that oral presentation was commonly used, especially in the teaching of procedural texts. Other techniques mentioned included interviews, role plays, group discussions, and picture descriptions. The assessment process was supported by clear instructions, the use of rubrics, a one-on-one delivery format, and sufficient time allocation for both preparation and performance. The teacher’s decisions in choosing assessment techniques were influenced by practicality, validity, student anxiety, and attention to key speaking components such as pronunciation and intonation. The study concludes that speaking assessments can be more effective when adapted to the classroom context and student needs through flexible and student-centred approaches.